NLRP3 downregulation enhances engraftment and functionality of adipose-derived stem cells to alleviate erectile dysfunction in diabetic rats - Luo, Chao; Peng, Yaqian; Zhou, Xiongcai; Fan, Junhong; Chen, Weihong; Zhang, Haibo; Wei, Anyang (Frontiers in Endocrinology, 2022)
Background: Transplantation of adipose-derived stem cells (ADSCs) is one of the most promising treatments for diabetic erectile dysfunction (DMED). However, the effect of high glucose on post-transplantation survival of stem cells limits the efficacy of ADSCs transplantation. Prolonging the survival time of ADSCs in vivo after transplantation has become a key issue to address ADSCs for DMED. In this study, we investigated the therapeutic effect of ADSCs by downregulating NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) and its novel mechanism in DMED. Methods: ADSCs were obtained by isolating subcutaneous fat from SD rats, and ADSCs were identified using lipogenic and osteogenic differentiation assays as well as flow cytometry analysis; shNLRP3 lentivirus with the best downregulation effect was screened, and shNLRP3 lentivirus (LV-shNLRP3) was transfected with ADSCs (ADSCsshNLRP3) to detect the apoptosis and reactive oxygen species (ROS) levels of ADSCs in each group under high glucose environment. In DMED rats, ADSCsLV-shNLRP3, ADSCsLV-control, or phosphate buffered saline (PBS) was administrated by intra-cavernous injection, and the normal rats served as normal controls. One week after injection, animal imaging was performed to track the ADSCs. Four weeks after injection, erectile function was evaluated by measuring the intra-cavernosal pressure and mean arterial pressure. Corpus cavernosum pyroptosis and endothelial function were examined by Western bloting and immunofluorescence. Results: NLRP3-mediated pyroptosis may be one of the pathogenic mechanisms of ED and DMED. ADSCs were isolated successfully, then The LV-shNLRP3 with the highest transfection efficiency was selected and successfully modified ADSCs. LV-shNLRP3 can protect the paracrine function of ADSCs under hyperglycemia through anti-apoptosis and anti-ROS deposition. Furthermore, ADSCsLV-shNLRP3 showed an advantage in the suppression of pyroptosis as compared to ADSCsLV-control. ADSCsLV-shNLRP3 group improved cavernous endothelial function and smooth muscle injury, and thus reversed erectile function, and was superior to ADSCsLV-control group. Conclusions: The NLRP3 Inflammasome-mediated pyroptosis may be involved in the formation of DMED. Intra-cavernous injection of ADSCsLV-shNLRP3 could suppress cavernosal pyroptosis, contributing to improved erectile function in DMED rats.